Mild Copper-Catalyzed, l-Proline-Promoted Cross-Coupling of Methyl 3-Amino-1-benzothiophene-2-carboxylate - Vilija Kederienė (MDPI AG, 2021)
Cu-catalyzed N-arylation is a useful tool for the chemical modification of aromatic heterocycles. Herein, an efficient carbon–nitrogen cross-coupling of methyl 3-amino-1-benzothiophene-2-carboxylate with a range of (hetero)aryl iodides using CuI, l-proline and Cs2CO3 in dioxane at moderate temperature is described. The procedure is an extremely general, relatively cheap, and experimentally simple way to afford the N-substituted products in moderate to high yields. The structures of the new heterocyclic compounds were confirmed by NMR spectroscopy and HRMS investigation.